Identification of Molecular Alterations Challenging Initial Pathologic Classification in Cases of Clinician-Initiated Next-Generation Sequencing Testing. Issue 6 (23rd June 2021) - Cho, Joseph H; Charnot-Katsikas, Angela; Segal, Jeremy; Pytel, Peter
Abstract: Objectives: Large gene panel next-generation sequencing (NGS) is a powerful tool capable of generating predictive data on cancer prognosis and response to specific therapeutic interventions. The utility of large panel NGS data on tumor classification, however, may be underappreciated because of a workflow that often circumvents the surgical pathologist. We sought to describe cases in which NGS data lead to an unanticipated change in tumor classification and to discuss current workflow practices of NGS testing that limit its use as a diagnostic adjunct. Methods: We performed a retrospective review to identify cases in which NGS testing uncovered data that led to a revision of the initial pathologic diagnosis that an outside or in-house pathologist had made. Results: Nine cases are presented in which NGS data provided insights that led to a revision of the original pathologic diagnosis. Distinctive molecular signatures, mutational signatures, fusions, or identification of viral sequencing provided the critical evidence on which these tumors were reclassified. Conclusions: The current workflow of NGS testing should always include the surgical pathologist as an active partner to ensure that the molecular results are fully reflected in the final diagnosis. In some instances, active participation by the surgical pathologist may require amendment of previously issued pathology reports.